Effects of seeding ratios and nitrogen fertilizer on ecosystem respiration of common vetch and oat on the Tibetan plateau - Zhang, Zhenhua; Duan, Jichuang; Wang, Shiping; Luo, Caiyun; Zhu, Xiaoxue; Xu, Burenbayin; Chang, Xiaofeng; Cui, Shujuan (Plant and soil, 2013)
Background and aims Few studies have investigated the effect of nitrogen (N) fertilizer on ecosystem respiration (Re) under mixed legume and grass pastures sown at different seeding ratios, and data are almost entirely lacking for alpine meadow of the Tibetan Plateau. Our aim was to test the hypothesis that although a combination of legumes with grass and N fertilizer increases Re the combination decreases Re intensity (i.e. Re per unit of aboveground biomass) due to greater increases in aboveground biomass compared to increases in Re. Methods This hypothesis was tested using different seeding ratios of common vetch (Vicia sativa L.) and oat (Avena sativa L.) with and without N fertilizer on the Tibetan plateau in 2009 and 2010. Re was measured using a static closed opaque chamber. Re intensity was estimated as the ratio of seasonal average Re during the growing season to aboveground biomass. Results Compared with common vetch monoculture pasture, mixed legume-grass pastures only significantly decreased Re intensity (with a decrease of about 75 %-87 %) in the drought year 2009 due to greater increases in aboveground biomass compared to increases in Re. There were no significant differences in Re and Re intensity among different seeding ratios of oat and common vetch in either year. N fertilizer significantly decreased Re intensity for common vetch monoculture pasture by 24.5 % in 2009 and 69.5 % in 2010 although it did not significantly affect plant production and Re. Conclusions From the perspective of forage yield and Re, planting mixed legume-grass pastures without N fertilizer is a preferable way to balance the twin objectives of forage production and mitigation of atmospheric greenhouse gas emissions in alpine regions.